Use of bauhinia forficata in the treatment of type 2 Diabetes mellitus (Research, Society and Development, 2022)
Diabetes mellitus is a chronic disease that affects the metabolism of carbohydrates, fats and proteins. The pathology has several classifications, among them type 1 (DM1) and 2 (DM2) and gestational DM, type 2 diabetes mellitus appears after a certain age, as a consequence of sedentary habits and obesity. Objective: To approach the medicinal use of Bauhinia forficata, as well as review its action in the treatment of diabetes. Methodology: The study is a review in the following databases: Scientific Electronic Librany Online (Scielo), Science, Pubmed, Lilacs, academia.edu, BDTD, CAPES journal website, ARCA, Redalyc, Elsevier, BMC, that follow the inclusion and exclusion criteria, with publication dates between 2000 and 2022. Results: It was found that the use of Bauhinia forficata extracts used in the research presented positive outcomes regarding its antidiabetic or hypoglycemic activity, evidenced by the continuous decrease in the glycemic profile and in the HGT values. Conclusion: Bauhinia forficata is a promising therapeutic alternative for the treatment of diabetes mellitus. It is necessary to apply more investments, mainly in research to better understand how its action with hypoglycemic effect and studies that support the benefits of its use in the treatment of Diabetes mellitus.